U-Module and readpen - Nazikussabah, Zaharudin; Khairul Amri, Abdul Aziz (2021)
U-Module and ReadPen is a combination of module with read pen which is meant for university students to read book/ module anytime with a built in speaker on the pen. U-Module and ReadPen provides definition (synonym) and also translation of the sentences into several languages. For example, from English to Malay. The most interesting part of U-Module and ReadPen is that it starts the narration audio and translation from anywhere the consumer want, by just pointing the pen on any sentences in the textbook.